Memahami Hakikat Hukum Islam - Ahsan, Muhmmad (Tasamuh: Jurnal Studi Islam, 2019)
Islamic law is the legal system based of Islamic teachings. To understand the meaning of Islamic law, necessary to understand the terms associated with Islamic law: the sharia, fiqh, usul fiqh, and Islamic law itself. The Sources of Islamic law are the Qur'an and Sunnah which iquipped with the ratio used to perform ijtihad. In general, there are two scopes of Islamic law, i.e. ibadah (worship) and muamalah. The worship regulates human relationships with his God, while the muamalah regulates human relationships with one another. Islamic law has different characteristics from other legal systems. Among of these characteristics is a perfect, elastic, universal, dynamic, systematic, and ta'aqquli- ta'abbudi. Islamic law has some basic principles too, such as not to burden, defined in stages, and consider the welfare and overall justice.